2010
DOI: 10.1007/s00464-010-1185-9
|View full text |Cite
|
Sign up to set email alerts
|

Elective laparoscopic cholecystectomy in the presence of common bile duct stent

Abstract: We conclude that LC in the presence of CBD stents poses significant risk to patients, particularly if they are left in-situ for long periods of time. Caution should be exercised in stenting a CBD with an intact gallbladder, particularly in those awaiting cholecystectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 28 publications
0
9
1
Order By: Relevance
“…Moreover, at long-term follow-up recurrent stones and cholangitis occur in 9–12% of cases after ERCP + ES, due to the subsequent modifications of the normal physiologic barrier and bactibilia [ 16 ]. Some studies have also reported an increased rate of difficult LC and higher conversion rates after ERCP, even if the previous endoscopic procedure had been only diagnostic [ 30 32 ]. As for the success rates, in the past several randomized multi-institutional trials have shown equivalence of single-stage versus the two-stage approach [ 5 , 11 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, at long-term follow-up recurrent stones and cholangitis occur in 9–12% of cases after ERCP + ES, due to the subsequent modifications of the normal physiologic barrier and bactibilia [ 16 ]. Some studies have also reported an increased rate of difficult LC and higher conversion rates after ERCP, even if the previous endoscopic procedure had been only diagnostic [ 30 32 ]. As for the success rates, in the past several randomized multi-institutional trials have shown equivalence of single-stage versus the two-stage approach [ 5 , 11 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among these periods, the development of CBDS between cholecystectomy and second ERC can be excluded because some reports have described that CBDS decreased in size and diameter, or disappeared in the majority of patients with biliary stent placement after EST [18, 19]. Moreover, it is unlikely for GS to enter the CBD during cholecystectomy because of small number of CBDS-associated complications reported after surgery [4, 12, 15, 16]. Thus, in the present study, recurrent CBDS is likely to have developed between first ERC and cholecystectomy, namely, during the waiting period for cholecystectomy in almost all patients.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, stenting and subsequent surgical treatment resulted in a higher incidence of postoperative complications. Nair et al [15] suggested that the placement of a bile duct stent for long duration before elective LC affected the operation time, conversion rate, bile leak rate and length of hospital stay. In contrast, Lee et al [16] reported there were no surgical complications regardless of whether biliary stenting was performed, and that the insertion of a stent was not a predictor of conversion to OC or a long operative time.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the ERC procedures, we compared the 2 groups according to the insertion of a biliary stent, and the timing of cholecystectomy after ERC. Nair et al 15 reported that the presence of a CBD stent was a risk factor for long operative duration and conversion to an open cholecystectomy. However, Verzhbitsky et al 16 showed no differences in the conversion rate in a stent insertion group and argued that having the stent in the CBD for a shorter period before surgery might eliminate the risk of conversion to an open operation.…”
Section: Discussionmentioning
confidence: 99%